Quantifying integrated SIV-DNA by repetitive-sampling Alu-gag PCR - Maud Mavigner; S. Thera Lee; Jakob Habib; Cameron Robinson; Guido Silvestri; Una O'Doherty; Ann Chahroudi (Elsevier, 2016)
Objectives: Although antiretroviral therapy (ART) effectively suppresses HIV-1 replication, it does not eradicate the virus and ART interruption consistently results in rebound of viraemia, demonstrating the persistence of a long-lived viral reservoir. Several approaches aimed at reducing virus persistence are being developed, and accurate measurements of the latent reservoir (LR) are necessary to assess the effectiveness of anti-latency interventions. We sought to measure the LR in SIV/SHIV-infected rhesus macaques (RMs) by quantifying integrated SIV-DNA. Methods: We optimised a repetitive sampling Alu-gagPCR to quantify integrated SIV-DNA ex vivo in ART-naïve and ART-experienced SIV/SHIV-infected RMs. Results: In ART-naïve RMs, we found the median level of integrated SIV-DNA to be 1660 copies and 866 copies per million PBMC during untreated acute and chronic SHIV infection, respectively. Integrated and total SIV-DNA levels were positively correlated with one another. In ART-treated RMs, integrated SIV-DNA was readily detected in lymph nodes and spleen and levels of total (3319 copies/million cells) and integrated (3160 copies/million cells) SIV-DNA were similar after a median of 404 days of ART. In peripheral blood CD4+ T cells from ART-treated RMs, levels of total (3319 copies/million cells) and integrated (2742 copies/million cells) SIV-DNA were not significantly different and were positively correlated. Conclusions: The assay described here is validated and can be used in interventional studies testing HIV/SIV cure strategies in RMs. Measurement of integrated SIV-DNA in ART-treated RMs, along with other reservoir analyses, gives an estimate of the size of the LR.